Menumbuhkan Empati dan Toleransi Mencetak Generasi Muda Bebas Bullying - Wafiq Alya Mustafida; Faizatul Ulya (Fakultas Teknik Universitas Cenderawasih, 2024)
Bullying behavior is now a special concern in all circles, especially in elementary schools. Starting from trivial teasing of his friend, in the long term it became a serious problem, because it had an emotional and psychological impact. Bullies are sometimes unaware of the actions they are taking, if they are very painful for the victim. In several cases found, children who bullied those who were older, more powerful, and felt famous among their friends. Meanwhile, those who are victims of bullying are those who are smaller in body size and come from economically disadvantaged families. There is a need to foster a sense of empathy and respect for children, whether they are perpetrators or victims.